Global mufti: the phenomenon of Yūsuf al-Qaraḍāwī - Gräf, Bettina; Qaraḍāwī, Yūsuf al-; Skovgaard-Petersen, Jakob (Hurst, 2009)
Introduction / Bettina Gr(c)Þf and Jakob Skovgaard-Petersen -- State of research / Bettina Gr(c)Þf -- Y¿±suf al-Qarad§Đ#w#± and al-Azhar / Jakob Skovgaard-Petersen -- Y¿±suf al-Qarad§Đ#w#± and the Muslim Brothers : the nature of a special relationship / Husam Tammam -- Y¿±suf al-Qarad§Đ#w#± as an authoritative reference (marji∫αiyya) / Motaz al-Khateeb -- Qarad§Đ#w#± in Europe, Europe in Qarad§Đ#w#±? The global mufti's European politics / Alexandre Caeiro and Mahmoud al-Saify -- Y¿±suf al-Qarad§Đ#w#± and the new Islamic TV / Ehab Galal -- Y¿±suf al-Qarad§Đ#w#± on women / Barbara Freyer Stowasser -- The concept of wasatὰyya in the work of Y¿±suf al-Qarad§Đ#w#± / Bettina Gr(c)Þf -- Qarad§Đ#w#±'s ması̀ʺahð̀Ł : from ideologue of the Islamic awakening to sponsor of transnational public Islam / Armando Salvatore. Islam / Armando Salvatore